Identify Hydrostatic Misconceptions Using Four Tier Diagnostic Tests With the Help of iSpring Suite 9 - Asri Nurhafsari; Febri Rismaningsih (Postgraduate, University of Mataram, 2022)
The study aims to identify students' misconceptions about hydrostatic concepts using the Four-Tier Diagnostic Test with the help of iSpring Suite 9. The methods used in this study are quantitative descriptive. The population in this study are all students of Strata 1 of the Faculty of Engineering of Universitas Islam Syekh-Yusuf who are studying Basic Physics. Sampling in this study through purposive sampling techniques that are subjective where the selection of samples is based on the consideration of the lecturer researcher concerned. Based on expert validation from the four-tier diagnostic test assisted iSpring Suite 9, it can be concluded that the instruments that have been developed are suitable for use for research. The reliability of the question is calculated using the Alpha Cronbach coefficient and a reliability value of 0.93 is obtained. This shows that the questions used in the research are reliable. The results of the study, which identified student misconceptions regarding hydrostatics, can be concluded that there are still many students who experience misconceptions with a percentage of 70.21% on the concept of hydrostatic pressure, 40.43% on Pascal law concept, 42.55% on the concept of Archimedes law. 46.81% on the concept of surface tension and 34.04% on the concept of capillarity. The percentage of overall misconceptions on the concept of hydrostatics falls into the high category